2012
DOI: 10.4172/2161-0495.1000121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atmospheric Particles and Several Model Particles of Particulate Matter Components on Human Monocyte-Derived Macrophage Oxidative Responses

Abstract: Atmospheric particles are ingested by alveolar macrophages in the lung. The macrophages release reactive oxygen species on ingesting the particles. The aim of this study was to investigate the effect of particulate matter components on the release of reactive oxygen species from macrophages. We compared the effect of particulate matter with that of several model particles of particulate matter components, such as diesel exhaust particles, silica particles, two kinds of carbon black particles (a laser printer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Moreover, we previously showed that a sample of PM induces much more superoxide from macrophages than a sample of silica with similar particle size (Ohyama et al, 2007) and that the superoxide response by macrophages to PM is similar to that of 3-nitrobenzanthrone-coated non-reactive particles (Ohyama et al, 2012). Therefore, the superoxide response by macrophages is not dependent on particle size only.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, we previously showed that a sample of PM induces much more superoxide from macrophages than a sample of silica with similar particle size (Ohyama et al, 2007) and that the superoxide response by macrophages to PM is similar to that of 3-nitrobenzanthrone-coated non-reactive particles (Ohyama et al, 2012). Therefore, the superoxide response by macrophages is not dependent on particle size only.…”
Section: Discussionmentioning
confidence: 84%
“…Of unique investment are a few natural air poisons that incorporate carbon monoxide, oxides of nitrogen, sulfur dioxide, ozone, lead, and particulate matter (PM) ("thoracic particles" [pm10] <10 μm in air motion facilitating distance across, "fine particles" [pm2.5] <2.5 μm, and "coarse particles" [pm10 to 2.5]). These contaminations are connected with expanded hospitalization [1] and mortality because of cardiovascular disease [2][3][4][5][6], particularly in persons with congestive heart disappointment, regular arrhythmias, or both [7,8]. The entrenched causal co-operations between dynamic and aloof smoking with coronary illness and stroke help the possibility of an unfavorable impact of PM on the cardiovascular framework.…”
Section: Types Of Particulatesmentioning
confidence: 99%